Characterization of single amino acid substitutions in the β2 integrin subunit of patients with leukocyte adhesion deficiency (LAD)-1 - Guan, Siyu (2015)
Leukocyte adhesion deficiency 1 (LAD-1) is caused by defects in the β2 integrin subunit. We studied 18 missense mutations, 14 of which fail to support the surface expression of the β2 integrins. Integrins with the β2-G150D mutation fail to bind ligands, possibly due to the failure of the α1 segment of the βI domain to assume an α-helical structure. Integrins with the β2-G716A mutation are not maintained in their resting states, and the patient has the severe phenotype of LAD-1. The β2-S453N and β2-P648L mutants support the expression of integrins and adhesion functions. They should be re-classified as polymorphic variants.